NILAI RUANG BERMUKIM SUKU MUNA: Kawasan Gunung Jati Kota Kendari - , ALIM BAHRI; , Prof. Ir. Sudaryono, M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In selecting and determining a site as a dwelling space, people surely has certain reasons and they will give its spatial value and meaning in a long period of time. Social interactions occurred in the selected dwelling space will raise local concepts that will be a pattern of attachment between the dwelling space and the people as the users of the space, so that the dwelling space and the people cannot be separated. It is because the people occupying the dwelling space believed that the space surely has meaning and they will give certain meaning to the dwelling space, thus raising an inseparable bond. The history of Muna tribeâs settlement in Gunung Jati has intensively been influenced by the public policies of the Local Government of Southeast Celebes Province to relocate forcefully the Muna tribeâs settlement in the areas of Gunung Jati. On the one hand, the relocation is done to provide protection over the areas of conservation forests as catchment areas. On the other hand, the protection policies have caused severe traumas for local community because they felt to be forcefully separated from both their social space and source of livelihood. This study was conducted by using a phenomenological approach with an explorative-inductive method to explore the value and meaning of the dwelling space in the Muna tribeâs settlement in Gunung Jati as well as to identify the local concepts that have grown in the living patterns of local community and produced knowledge that they will defend their dwelling space by applying certain ways, methods, strategies, and concepts to exist, survive and retain their dwelling site . Results of the study show that the local concepts that have naturally grown in a long historical process amidst the social life of the Muna tribeâs community in Gunung Jati reflected certain ways or strategies to preserve a spirit of solidarity and a sense of caring in a homogenous community. The Muna tribeâs community in Gunung Jati regarded that by the homogenous community with the same historical, economic, social and cultural background as well as the similar social relationship will be able to exist in preserving the areas of Gunung Jati as the source of strategic livelihood. Moreover, these local concepts become the bases for the development of value and meaning for the dwelling space of the Muna tribeâs settlement in Gunung Jati as the social sphere to show tribal territorial existence and identity and a natural space as the source of livelihood to reach a better economic life. Theoretical knowledge as a contribution of the study includes the concepts of value and meaning for the dwelling space of the Muna tribeâs settlement in Gunung Jati that will be the appropriate bases for the local government to issue the public policies in a wise and humanist manner, particularly in planning the spatial order amidst the areas of conservation forests for preventing the local community from being forcefully separated from their source of livelihood